Pure pedagogy: educational tools to maintain student interest and engagement in language courses - Fisher, Garrett (2017)
In 2017, language educators are considering the best ways to educate students because ofthe increase in technology use. This article addresses three topics that language instructorsfrequently consider: (1) the use of technology with current students, (2) appropriate methods and technologies for use with current generations, and (3) the implementation of change to increase student engagement. This article argues that engagement is a critical aspect in language classrooms and knowledge of current students, technology, and second language teaching methods can help maintain interest and participation with students. While it is futile to argue for a single method as the most optimal way to teach a language, this paper offers information on multiple methods and evaluates their usage with current generations while touching on the considerations that must be taken into account while implementing technology with students in language classrooms. This research utilizes Task-Based Language Teaching (TBLT) as a main base for the methodological framework, yet other methods are considered because technology and additional methods, such as the Grammar-Translation Method, the Natural Method, Community Language Learning (CLL), Total Physical Response (TPR), and Teaching Proficiency through Reading and Storytelling (TPRS) can be integrated within TBLT to maintain the interest and engagement of current language students.